Presumed unconstrained dispersal of Aedes aegypti in the city of Rio de Janeiro, Brazil - Freitas, Rafael Maciel de (2009)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Entomologia. Laboratório de Transmissores de Hematozoários. Rio de Janeiro, RJ. Brasil.